Four new species of the Neotropical spider genus Enna (Araneae, Lycosoidea, Trechaleidae) from Brazil - Da Silva, Estevam L. Cruz; Lise, Arno A. (Zootaxa, 2009)
Currently, 24 species are known for the spider genus Enna O. Pickard-Cambridge, from North, Central and South America, of which six are known from Brazil. In this study four new species are described and illustrated based on female specimens from the Southeastern and Southern Brazilian states of Minas Gerais, São Paulo, Rio de Janeiro and Paraná. Enna trivittata sp. n., E. segredo sp. n., E. meridionalis sp. n. and E. caparao sp. n. can be distinguished from all known species by the general shape of the epigynum. New records in Brazil are presented for E. braslandia Silva, Lise & Carico and E. redundans (Platnick).